Les boursiers de la Fondation Ford et la recomposition des sciences sociales brésiliennes - Letícia Canêdo (Cahiers de la Recherche sur l'Education et les Savoirs)
This article presents the first results of a research on the connections between international circulation of university professors and graduate students, and the genesis of Political Sciences as an academic field in Brazil. The text focuses on a small group of former Foundation Ford fellows who, after obtaining a PhD degree in the United States, fought to obtain recognition of their competences within the Social Sciences field in Brazil between 1960 and 1980. They managed to affirm their intellectual authority to analyze political phenomena and to define Political Sciences as a scientific discipline in Brazilian universities, research centers and scientific associations, State institutions, and consulting market. The study seeks to understand what ensures to certain groups, in certain moments of reorganization of the political space, the strength to succeed in the academic and political fields.